2018
DOI: 10.1111/ced.13665
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose weekly methotrexate used to treat cutaneous Rosai-Dorfman disease

Abstract: Click https://www.wileyhealthlearning.com/ced.aspx for the corresponding questions to this CME article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Al-Khateeb (12) found that corticosteroids were the least effective treatment for CRDD. However, low-dose methotrexate has been found to be an effective treatment (11,13). The current patient initially demonstrated resistance to prednisone but then responded well to methotrexate.…”
Section: Diagnosis: Cutaneous Rosai-dorfman Diseasementioning
confidence: 72%
“…Al-Khateeb (12) found that corticosteroids were the least effective treatment for CRDD. However, low-dose methotrexate has been found to be an effective treatment (11,13). The current patient initially demonstrated resistance to prednisone but then responded well to methotrexate.…”
Section: Diagnosis: Cutaneous Rosai-dorfman Diseasementioning
confidence: 72%
“…In our case, the limited extension of lesions prompted the use of methotrexate over MAP2K1/2 inhibitors as a first‐line treatment, mainly because of the restricted access and the greater risk of toxicities of the latter. Low‐dose methotrexate has been used in several case reports of cutaneous RDD leading to partial or complete responses in the majority of cases 7 . Methotrexate increases the inhibition of isoprenylcysteine carboxyl methyltransferase inducing the hypomethylation of RAS by almost 90% 8 and thus could act by inhibiting directly the MAPK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Low‐dose methotrexate has been used in several case reports of cutaneous RDD leading to partial or complete responses in the majority of cases. 7 Methotrexate increases the inhibition of isoprenylcysteine carboxyl methyltransferase inducing the hypomethylation of RAS by almost 90% 8 and thus could act by inhibiting directly the MAPK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Topical and intralesional corticosteroids and topical imiquimod have been used to treat cutaneous RDD, with the effects varying from mild to total improvement [ 4 , 6 ]. For the treatment of refractory or extensive disease, there is some evidence of thalidomide [ 6 ], dapsone [ 9 ], imatynib [ 5 ] and low-dose weekly MTX as monotherapy or combined with steroids being efficacious [ 15 , 16 ]. A successful, total remission of cutaneous RDD after 11 months of treatment with 15 mg of MTX per week and triamcinolone injections prompted the introduction of this treatment [ 16 ].…”
Section: Discussionmentioning
confidence: 99%